Reinterpreting the Normal Mode of Submarine in Archipelagic Sea Lane Passage - Yoga, Pornomo Rovan Astri; Alverdian, Indra (UI Scholars Hub, 2024)
Today, many experts of maritime powers take it for granted that a foreign submarine has the right of submerged passage in an archipelagic sea lane. By using the 1969 Vienna Convention on the Law of Treaties (VCLT) as a tool of interpretation, this paper tries to decipher whether a submerged passage is permissible or not in archipelagic sea lane passage. This paper found that the submerging in an archipelagic sea lane passage is not a generally accepted interpretation of “normal mode” in Article 53 of the 1982 United Nations Convention on the Law of the Sea (UNCLOS). The writers discovered on one hand, the result of the travaux preparatoir means of interpretation appears to be in favor of the submerged passage being included within the meaning of “normal mode”. The textual interpretation, on the other hand, emphasizes the exclusion of submerged passage from both transit passage and archipelagic sea lane passage. In the case of an archipelagic sea lane passage, the exclusion of submerged passage weighs more than the transit passage. Therefore, based on VCLT 1969, which says that the textual interpretation takes precedence over the interpretation of travaux préparatoires, the submerged passage is not a widely accepted interpretation.